Hepatic dysfunctions in COVID-19 patients infected by the omicron variant of SARS-CoV-2 - Zhang, Jianguo; Zhao, Daguo; Hu, Jianhui; Huang, Xing; Gu, Qingqing; Tao, Zhimin (Frontiers in Public Health, 2022)
Background Presently, the omicron variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) dominates amid the coronavirus disease 2019 (COVID-19) pandemic, but its clinical characteristics with intrinsic severity and organ tropism remain understudied. Methods We reported 1,001 mild COVID-19 patients that were infected with the omicron variant of SARS-CoV-2 and hospitalized in China from February to June 2022, including their demographic information, medical/immunization history, clinical symptom, and hematological profile. Patients with one-, two- and three-dose vaccination were compared to assess the vaccine effectiveness. Importantly, liver damage caused by the omicron variant infection was evaluated, in comparison to that caused by the wild-type or the delta variant SARS-CoV-2 infection. Results For the reported COVID-19 patients infected by the omicron variant of SARS-CoV-2, their median age was 36.0 [interquartile range (IQR): 26.0-50.0] and 49.7% were female. Hypertension, diabetes, and bronchitis were the leading comorbidities, and asymptomatic patients took up a major portion (61.2%). While most hematological parameters revealed the alleviated pathogenicity, full vaccination or booster shot showed effective protection against clinical severity. Furthermore, liver damages caused by viral infection of the omicron variant were largely attenuated when compared to those by infection of the wild-type or the delta variant SARS-CoV-2. Conclusions Our results supported that the viremic effect of the omicron variant tended to be modest, while the liver damage caused by this strain became milder than the previous circulating variants.